1989
DOI: 10.1288/00005537-198905000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Small fenestra stapedotomies with and without ktp laser: A comparison

Abstract: The results of 33 small fenestra stapedotomies performed using conventional techniques were compared with the results of 33 stapedotomies performed using the argon or KTP laser. The ossicular chain was reconstructed using a Teflon wire piston of 0.6 mm diameter, and follow-up was at least 1 year. Over-closure of the air-bone gap or closure to within 10 dB was accomplished in 91% of the laser-treated group versus 72% of the conventionally treated group (p less than 0.10). The hearing results were statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 6 publications
1
66
0
4
Order By: Relevance
“…Silverstein et al [20] reported a higher incidence of postoperative vertigo in the laser stapedotomy group compared to the conventional group (39% vs. 12%, respectively). However, in another study, there was no difference between these groups in video-oculographic findings at postoperative week 1 [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Silverstein et al [20] reported a higher incidence of postoperative vertigo in the laser stapedotomy group compared to the conventional group (39% vs. 12%, respectively). However, in another study, there was no difference between these groups in video-oculographic findings at postoperative week 1 [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In stapedotomy, the blood is located in the vestibule, possibly causing vertigo. Several authors report (transient) vertigo following KTP or argon laser stapedotomy in patients, ranging from 6.6 to 39% [1,4,5,6]. As blood in the vestibule could be absorbed in time, clinical symptoms of vertigo subside.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of the laser light through the perilymph may result in the absorption of residual energy in the neuroendothelium in the vestibule. Authors have suggested that this could explain the (temporary) vertigo complaints in patients after KTP laser-assisted stapedotomy [1,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Nessas revisões não usamos o laser [12][13][14][15][16] e mantivemos a técnica tradicional da cirurgia 1,2,[17][18][19][20] , com o emprego de ganchos especializados, usando raramente brocas afiadas para a abertura da base do estribo. A prótese empregada nas revisões foi na grande maioria a de teflon de 0,6mm ou 0,4mm de espessura e também em alguns casos a prótese de aço e teflon.…”
Section: Introductionunclassified